POS-ISLAMISME “ILMU” EKONOMI ISLAM DI ERA URBAN DAN MULTIKULTURALISME - Addi Rahman (Islam Realitas: Journal of Islamic and Social Studies, 2015)
Islamic economics was born from the spirit of Islamization of science. It was a response to the problems and realities of Muslims who face malaise in the middle of the feud ideologies of capitalism and socialism. However, after the Islamisation process took place, there were some fundamental problems: the hegemony of the market, popularism of Islamic economics as a result of the crisis of epistemology. This is the new face of Islamic economics stub of post-Islamism. The economic problems, particularly in Indonesia, should be viewed as a complex things, then analyze and tie the formulation of solution must alsobe done by the complex or plural approach. For this purpose, it would be required a pilot of a systematic framework of Islamic economics epistemology in the world view of Islam. At this point, indonesialize the Islamic economics is part of efforts to establish an economic framework in accordance with the spirit and rich culture of indigenous people of Indonesia. Moreover, in the context of the postmodernist paradigm of economic development, local wisdom should be involved in economic development which is an effort to actualize the sustainable economic development Sebagai disiplin ilmu, ekonomi Islam lahir dari semangat islamisasi ilmu pengetahuan. Ia merupakan respon terhadap persoalan dan realitas umat muslim yang mengalami malaise di tengah perseteruan ideologi kapitalisme dan sosialisme. Namun, setelah proses islamisasi itu berlangsung, terdapat persoalan mendasar: yaitu hegemoni pasar, popularisme ekonomi Islam sebagai dampak dari krisis epistemologi. Inilah yang menjadi wajah baru rintisan ilmu ekonomi islam pos-islamisme. Berangkat dari permasalahan ekonomi, khususnya di Indonesia, semestinya dilihat secara kompleks, maka mengurai dan merajut formulasi solusinya harus pula dengan pendekatan yang kompleks atau plural. Untuk tujuan ini, maka diperlukan sebuah rintisan kerangka epistemologi ekonomi Islam yang tersistem dalam world view Islam Pada titik ini, mengindonesiakan ekonomi Islam merupakan bagian dari upaya membentuk kerangka ekonomi yang sesuai dengan nafas budaya dan kearifan lokal masyarakat Indonesia yang sangat kaya. Terlebih, dalam konteks paradigma pembangunan ekonomi pascamodernis, semestinya melibatkan kearifan lokal dalam pembangunan ekonomi yang merupakan upaya mewujudkan pembangunan ekonomi yang berkelanjutan (sustainable development)